2019
DOI: 10.3390/ijms20153791
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions Between Reactive Oxygen Species and Autophagy in Kidney Disease

Abstract: Reactive oxygen species (ROS) are highly reactive signaling molecules that maintain redox homeostasis in mammalian cells. Dysregulation of redox homeostasis under pathological conditions results in excessive generation of ROS, culminating in oxidative stress and the associated oxidative damage of cellular components. ROS and oxidative stress play a vital role in the pathogenesis of acute kidney injury and chronic kidney disease, and it is well documented that increased oxidative stress in patients enhances the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 203 publications
(226 reference statements)
1
71
0
2
Order By: Relevance
“…Nrf2 is a basic region‐leucine zipper (bZip) transcription factor that acts as an efficient and pivotal line of defensive to counteract environmental insults and endogenous stressors . Under normal conditions, the Nrf2 is tightly controlled in cytoplasm by its inhibitory binding protein Kelch‐like ECH‐associated protein 1 (Keap1) . In adaptation to different stress conditions, Nrf2 translocates into the nucleus, in which Nrf2 forms heterodimers with small musculoaponeurotic fibrosarcoma protein (MAF) K, G, and F, and then binds to the antioxidant response element (ARE) and initiates the transcription of many antioxidant and Phase II detoxification enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a basic region‐leucine zipper (bZip) transcription factor that acts as an efficient and pivotal line of defensive to counteract environmental insults and endogenous stressors . Under normal conditions, the Nrf2 is tightly controlled in cytoplasm by its inhibitory binding protein Kelch‐like ECH‐associated protein 1 (Keap1) . In adaptation to different stress conditions, Nrf2 translocates into the nucleus, in which Nrf2 forms heterodimers with small musculoaponeurotic fibrosarcoma protein (MAF) K, G, and F, and then binds to the antioxidant response element (ARE) and initiates the transcription of many antioxidant and Phase II detoxification enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive fat also induces constitutive activation of mTORC1 that directly inhibits AMPK activity, suggesting a link between mTOR and AMPK [156,157]. However, AMPK-mediated activation of autophagy protects against renal injury, particularly in AKI [158]. Regarding metabolic disease-related CKD, Yamahara et al demonstrated that obesity significantly suppressed autophagy in PTC of both mice and humans.…”
Section: Ampk and The Regulation Of Renal Autophagy And Mitophagymentioning
confidence: 99%
“…Autophagy is an evolutionarily conserved, dynamic process of degradation of intracellular organelles and macromolecules by lysosomal hydrolases [7]. Previous studies suggest that the low level of autophagy is shown when AKI is detected in septic AKI models [43,44].…”
mentioning
confidence: 99%